Effectiveness of Structured Teaching Programme on Knowledge Regarding Maintenance of Warm Chain in Prevention of Hypothermia in Newborn Babies: A Quasi-experimental Study - Thakur, Pooja; Puri, Amita; Dogra, Reena (International Journal of Nursing Research, 2023)
Background: Hypothermia is common in newborn born at hospitals (prevalence range, 32–85%) and homes (prevalence range, 11–92%), even in tropical environments. The lack of thermal protection is still an underappreciated major challenge for newborn survival in developing countries. Aim: The main was to assess the effectiveness of structured teaching programme (STP) on knowledge regarding maintenance of warm chain in the prevention of hypothermia in newborn babies among B.Sc. Nursing 4th-year students. Methodology: A quasi-experimental research design was used. A total of 116 students of B.Sc Nursing 4th-year were selected through convenient sampling. Self-structured questionnaire comprised 35 questions was used. After pre-test, STP was provided to the samples using powerpoint presentations. The post-test was conducted thereafter and knowledge scores of both pre-test and pot-test were compared. Results: In pre-test experimental group, 51 (87.9%) had average knowledge, 7 (12.1%) had below-average knowledge, whereas in post-test experimental group, 56 (96.6%) had good knowledge, and 2 (3.4%) had average knowledge. In pre-test control group, 49 (84.5%) had average knowledge, 9 (15.5%) had below-average knowledge, whereas in post-test control group 52 (89.7%) had average knowledge, and 6 (10.3%) had below average knowledge. It was found that there is significant change in post-test knowledge score of the experimental group with t value 62.916 at the degree of freedom at 57 at 0.05 level of significance. Conclusion: The findings concluded that the STP was effective in increasing knowledge of B.Sc nursing 4th-year students.